(untitled) (The Planet, 2023)
Background: The incidence of postoperative hypotension(POH) is linked to serious complications. Postoperativepatients in the general-care unit who did not experienceIOH had a lower threshold for blood pressure monitoring,although the relationship between this threshold andoutcomes is poorly understood. Objective: To determinewhether or not postoperative hypotension is linked toserious clinical complications in those whose bloodpressure didn’t drop while they were having surgery.Method: The location of this cross-sectional study, whichtook place between January 2020 and January 2023, wasthe Department of Anaesthesiology at the Holy Family RedCrescent Medical College Hospital in Dhaka, Bangladesh.This study was carried out between the years of 2020 and2023. The inquiry called for a sample size of 200participants, and that number was intentionally chosen. Results: In our study, 34% werebetween 50 to 59 years age group and 3.5% were more than 80 years old. Maximum patients(54%) were female patients and minimum patients (46%) were male patients. Maximumpatients (32%) had undergone a open reduction of fracture surgery and the minimum numberof patients (5%) had undergone colon surgery. Maximum patients had hypertension (51.75%)and diabetes (36.25%). And a minimum number of patients (4.5%) had myocardial infarction.Conclusion: Patient and surgical variables, such as age and kind of operation, have beenshown to affect the association between IOH and bad result in clinical practice.